HaCaT cells as a model system to study primary cilia in keratinocytes. Issue 8 (23rd June 2022) - Blanchard, Gabriela; Pich, Christine; Hohl, Daniel
Abstract: Primary cilium (PC) is a microtubule‐based organelle found on the apical surface of most mammalian cell types, playing a role in development and tissue homeostasis. Ciliopathies are a rapidly growing group of human diseases characterized by disordered cilium. PC plays an important role in pathogenesis of basal cell cancer, the most common human malignancy. A significant increase in ciliation has been observed in the epidermis of atopic dermatitis and psoriasis patients. Spontaneously immortalized human keratinocytes, HaCaT are a model to study the epidermal homeostasis and pathophysiology. In contrast to what has been previously described, here, we show that HaCaT can be efficiently ciliated. In HaCaT cells, differentiation significantly increased the number of ciliated cells and we were able to analyse in detail the ciliary length progression with duration of differentiation. As the number of recognized ciliopathies continues to increase, the importance of ciliary models also rises. Even though keratinocytes do not become as highly and rapidly ciliated as cell lines frequently used in ciliary studies, they are a better model for the study of skin ciliopathies. Detailed progression of ciliation in HaCaT could serve as the basis for ciliary studies in this cell line.